Pengaruh Motivasi dan Tipe Perilaku Kerja Pegawai Generasi Z terhadap Kualitas Layanan di Hotel Amaris Slipi Jakarta - Sri Wahyuni; Ahmad Yani; Febby Permatasari Kusumah; Phintoko Akhbar Akriyono (Journal on Education, 2023)
This research aims to determine the influence of work motivation and work behavior on the service quality of the Amaris Slipi Hotel. The research method used is the Quantitative Associative method. The population in this study is 100 generation z employees of the Amaris Slipi Hotel in 2023. The sampling technique uses a sampling technique with a sample of 100 people as respondents. Data collection methods are observation and questionnaires. The data analysis methods used were validity tests, reliability tests, simple and multiple linear regression tests, correlation coefficient tests (R), determination tests (R Square), and hypothesis tests (F test and t test). The research results show that Work Motivation partially has a significant effect on Service Quality with the regression equation Y=14.37+0.726X1 and an influence contribution of 37.4%. Hypothesis testing obtained a value of t_count > t_table or (6.018 > 1.985). Work Behavior partially has a significant effect on Service Quality with the regression equation Y=14.981 + 0.43 Work Motivation and Work Behavior simultaneously have a significant effect on Service Quality with the regression equation Y = 10.260 + 0.617X1 + 0.226X2 and an influence contribution of 41.1%, the hypothesis test obtained a value of F_count > F_tabel or (33.878 > 3.091)